2011
DOI: 10.1002/ijc.25801
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and outcome of breast needle core biopsy diagnoses of lesions of uncertain malignant potential (B3) in abnormalities detected by mammographic screening

Abstract: In the setting of breast cancer screening, 5-9% of needle core biopsies are diagnosed as lesions of uncertain malignant potential (B3). The management of these lesions is potentially problematic as the data on their outcome remains limited. In our study, we aim to assess the outcome of screen-detected lesions diagnosed as B3 in a large series to validate previous studies and to characterize the malignant lesions detected after a B3 diagnosis. Therefore, the results of 1,025 needle core biopsies of women screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
65
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 39 publications
(52 reference statements)
17
65
3
2
Order By: Relevance
“…Seven studies [7,22,36,38,39,42,44] are comparable to our study considering the homogeneity of series reported (US 14G NCB). These studies report a range of underestimation rate between 15 and 47 %, and our value of underestimation rate (47.8 %) results to be very close to superior limit of this range.…”
Section: Papillary Lesions With Epithelial Atypiasupporting
confidence: 89%
See 1 more Smart Citation
“…Seven studies [7,22,36,38,39,42,44] are comparable to our study considering the homogeneity of series reported (US 14G NCB). These studies report a range of underestimation rate between 15 and 47 %, and our value of underestimation rate (47.8 %) results to be very close to superior limit of this range.…”
Section: Papillary Lesions With Epithelial Atypiasupporting
confidence: 89%
“…These studies report a range of underestimation rate between 4 and 12.9 %, and our value of underestimation rate (13.2 %) results to be very close to superior limit of this range. The five larger series [7,36,38,39,42] using 14G NCB reporting more than one-hundred cases (160, 131, 155, 203 and 191) show a wide range of underestimation rate (5, 9, 12.9, 6 and 5 % respectively).…”
Section: Papillary Lesions Without Epithelial Atypiamentioning
confidence: 94%
“…Similarly to previous results, we found AEPDT to be the B3 lesion with the highest rate of finally detected malignancy (40 % [7], 50 % [10]). 30.4 % (7/23) of the diagnoses of AEPDT in minimally invasive biopsy were not proved as atypical ductal hyperplasia (ADH) after excision surgery but were upgraded to a malignant diagnosis, mainly to DCIS diagnosis (85.7 %).…”
supporting
confidence: 90%
“…ADH is recognized both as a risk indicator and a non-obligate precursor of low-grade DCIS and invasive BC though the risk of development of invasive carcinoma is smaller than that observed with DCIS. 23 Unlike low-grade DCIS, high-grade DCIS is not a part of LGBNF. When high-grade DCIS progresses to or presents with invasive cancer, the latter is usually of high-grade and they share the same pattern of genetic aberrations.…”
Section: Low-grade Breast Neoplasia Family: Morphologymentioning
confidence: 97%